2016
DOI: 10.17977/um015v44i22016p111
|View full text |Cite
|
Sign up to set email alerts
|

Respon Tutur Siswa Autis Terhadap Tutur Direktif Guru Dalam Interaksi Pembelajaran Di Kelas

Abstract: Abstract:The aim of this study is to describe the form, function and response strategies from autistic studentson the teachers' directive in the classroom. This study used a case study. The results showed that there are two categories of the students' spoken responses: (1) speech production in the form of assertive, directive, commissive and expressive; and (2) the speech responses are based on the senses including auditory, visual and emotions. In addition, the function of the students' responses is categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Due to the repeated questions, they expressed unhappiness. The speech (9) and (11) indicated this symptom. The data showed that a dislike of the autistic child to receive questions from her partner was expressed by saying sakit kepala (headache) while holding the head.…”
Section: A the Statement Of Happinessmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to the repeated questions, they expressed unhappiness. The speech (9) and (11) indicated this symptom. The data showed that a dislike of the autistic child to receive questions from her partner was expressed by saying sakit kepala (headache) while holding the head.…”
Section: A the Statement Of Happinessmentioning
confidence: 94%
“…However, since Hasan did not immediately answer the question, in the speech (8) the partner provided an example of the expression that Hasan must say to Udin. In the speech (9) Hasan showed his gratitude to Udin after he received the soup noodle.…”
Section: Aa2 (Autistic Child 2): "Terima Kasih Udin" (Thank You Udin)mentioning
confidence: 99%
See 1 more Smart Citation